John of Damascus, first apologist to the Muslims : the Trinity and Christian apologetics in the early Islamic period - Janosik, Daniel; Riddell, Peter G. (2016)
Much of the world today is convulsed in an epic struggle between the Christian West and Islam. Scholars seeking to understand the issues look back in history to unearth the roots of this conflict. Of great value in this effort are the writings of an eyewitness, a devoted Christian who served as chief financial officer of the Umayyad Empire and wrote at the time Islam was developing. John of Damascus (675-750) authored two major works, the Heresy of the Ishmaelites and the Disputation between a Christian and a Saracen, to provide an apologetic response to Islam from a Christian perspective. His writings shed light on many questions that are pertinent today: When was the Qur'an actually written? What was the role of the powerful caliph Abd al-Malik in the making of Muhammad? How did the theological issues related to the deity of Christ and the Trinity develop in the early days of Islam? This book delves into the life of John and studies his apologetic writings in detail, utilizing the first English translation from the critical text. It seeks to address these questions thoughtfully, provide valuable insights from the past, and then equip today's church as it engages with Islam--
The development of the Trinity through controversy -- John of Damascus: controversies regarding his life and work -- John's Islamic context -- The early formation of Islam -- Theological development of Islam -- Heresy of Ishmaelites: authenticity and analysis -- Disputation between a Christian and a Saracen: authenticity and transmission -- Analysis of the disputation between a Christian and a Saracen -- The Trinitarian beliefs of John of Damascus -- The Development of John's apologetic approach -- The apologetic successors of John -- Concluding thoughts.
Includes bibliographical references (pages 277-290) and index.
Keywords: John, -- of Damascus, Saint; John, -- of Damascus, Saint; 600-1500; Trinity -- History of doctrines -- Middle Ages, 600-1500.; Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Christianity; Interfaith relations; Islam; Trinity -- History of doctrines -- Middle Ages